Downregulation of ULK1 by microRNA‐372 inhibits the survival of human pancreatic adenocarcinoma cells. Issue 9 (10th August 2017) - Chen, Hongxi; Zhang, Zhipeng; Lu, Yebin; Song, Kun; Liu, Xiwu; Xia, Fada; Sun, Weijia
Abstract : Dysregulation of microRNA (miRNA) expression in various cancers and their role in cancer progression is well documented. The purpose of this study was to investigate the biological role of miR‐372 in human pancreatic adenocarcinoma (HPAC). We collected 20 pairs of HPAC tissues and adjacent non‐cancerous tissues to detect miR‐372 expression levels. We transfected BXPC‐3 and PANC‐1 cells with miR‐372 inhibitor/mimics to study their effect on cell proliferation, apoptosis, invasion, migration and autophagy. In addition, miR‐372 mimics and a tumor protein UNC51‐like kinase 1 (ULK1) siRNA were co‐transfected into BXPC‐3 and PANC‐1 cells to explore the mechanism of miR‐372 and ULK1 on HPAC tumorigenesis. We found that the expression of miR‐372 was markedly downregulated in HPAC cells compared to adjacent normal tissues. Furthermore, functional assays showed that miR‐372 inhibited cell proliferation, invasion, migration and autophagy in BXPC‐3 and PANC‐1 cells. An inverse correlation between miR‐372 expression and ULK1 expression was observed in HPAC tissues. Downregulation of ULK1 inhibited the overexpression effects of miR‐372, and upregulation of ULK1 reversed the effects of overexpressed miR‐372. Finally, we found that silencing ULK1 or inhibiting autophagy partly rescued the effects of miR‐372 knockdown in HPAC cells, which may explain the influence of miR‐372/ULK1 in HPAC development. Taken together, these results revealed a significant role of the miR‐372/ULK1 axis in suppressing HPAC cell proliferation, migration, invasion and autophagy. Abstract : Human pancreatic adenocarcinoma tissue downregulated miR‐372, and miR‐372 plays a negative role on HPAC cell growth. ULK1 as a direct target of miR‐372, and a reversed correlation existed between miR‐372 expression levels and ULK1 mRNA levels in HPAC. The loss of phosphorylation of ULK1 on Ser 555 induced by miR‐372 inhibits HPAC cell autophagy.